Designs of Charge-Balanced Edge Termination Structures for 3.3 kV SiC Power Devices Using PN Multi-Epitaxial Layers - Sangyeob Kim; Ogyun Seok (Micromachines)
We demonstrated 3.3 kV silicon carbide (SiC) PiN diodes using a trenched ring-assisted junction termination extension (TRA-JTE) with PN multi-epitaxial layers. Multiple P+ rings and width-modulated multiple trenches were utilized to alleviate electric-field crowding at the edges of the junction to quantitively control the effective charge (Qeff) in the termination structures. The TRA-JTE forms with the identical P-type epitaxial layer, which enables high-efficiency hole injection and conductivity modulation. The effects of major design parameters for the TRA-JTE, such as the number of trenches (Ntrench) and depth of trenches (Dtrench), were analyzed to obtain reliable blocking capabilities. Furthermore, the single-zone-JTE (SZ-JTE), ring-assisted-JTE (RA-JTE), and trenched-JTE (T-JTE) were also evaluated for comparative analysis. Our results show that the TRA-JTE exhibited the highest breakdown voltage (BV), exceeding 4.2 kV, and the strongest tolerance against variance in doping concentration for the JTE (NJTE) compared to both the RA-JTE and T-JTE due to the charge-balanced edge termination by multiple P+ rings and trench structures.